1996
DOI: 10.1530/jrf.0.1070265
|View full text |Cite
|
Sign up to set email alerts
|

Role of high molecular weight seminal vesicle proteins in eliciting the uterine inflammatory response to semen in mice

Abstract: Mating evokes a characteristic pattern of molecular and cellular events in the rodent reproductive tract, including an infiltration of the endometrial stroma and uterine lumen with activated macrophages and granulocytes, which closely resembles a classic inflammatory response. Previous studies in mice indicate that these cellular changes are associated with, and are largely a consequence of, an upregulated synthesis and release of granulocyte-macrophage colony-stimulating factor (GM-CSF) from the uterine epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
145
1
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(165 citation statements)
references
References 11 publications
12
145
1
1
Order By: Relevance
“…The inflammatory response occurring at insemination can be attributed to factors within seminal plasma, as opposed to sperm. This conclusion is based in findings that show the lack of a uterine inflammatory response after mating mice with seminal vesicle deficient stud males [8], suggesting that the factors initiating this inflammatory cascade originate in the seminal vesicle, where the majority of seminal plasma is produced. The upregulation of cytokines within the human cervix and murine uterus and has been specifically linked with the seminal plasma cytokine TGFβ [7,11].…”
Section: Post-insemination Inflammationmentioning
confidence: 99%
See 2 more Smart Citations
“…The inflammatory response occurring at insemination can be attributed to factors within seminal plasma, as opposed to sperm. This conclusion is based in findings that show the lack of a uterine inflammatory response after mating mice with seminal vesicle deficient stud males [8], suggesting that the factors initiating this inflammatory cascade originate in the seminal vesicle, where the majority of seminal plasma is produced. The upregulation of cytokines within the human cervix and murine uterus and has been specifically linked with the seminal plasma cytokine TGFβ [7,11].…”
Section: Post-insemination Inflammationmentioning
confidence: 99%
“…After uterine epithelial cells are exposed to seminal factors, the surge of pro-inflammatory cytokines and chemokines (as stated above) causes an infiltration of inflammatory leukocytes. In addition to neutrophils a large number of antigen presenting cells (APCs) are recruited into the uterine endometrium, including macrophages and dendritic cells (DCs) expressing high levels of MHC class II [60,8]. This response has now been well characterised in other species including rabbit, horse, pig, and human [61][62][63][64]12].…”
Section: Post-insemination Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically studies in mice [1,2] and pigs [3] found SP to be essential for implantation, interacts with uterine epithelial cells and induces a postmating inflammatory cascade. Several inflammation-inducing proteins present in SP are transforming growth factor b, [1,4], prostaglandin E and interleukin-8 [7].…”
Section: Discussionmentioning
confidence: 99%
“…A variety of studies first in animal models such as mice, [1,2] and pigs [3], and then in human in vitro cell culture models [4][5][6] indicate that seminal plasma (SP) reaching the endometrial cavity after intercourse may have an important role in affecting the uterine receptivity. SP contains a variety of factors such as Transforming Growth Factor b, [1,4], prostaglandin E and interleukin-8 [7], that may trigger a cascade of events through pro-inflammatory cytokines synthesis leading to maternal endometrial immunomodulation increasing uterine receptivity.…”
Section: Introductionmentioning
confidence: 99%